THE ANALYSIS OF BUYING INTENTION OF GENERATION Z CONSUMERS - Izaak, Wilma Codelia; Hariyana, Nanik; Sholihah, Dienni R.; Ardyanfitri, Helmina (Jurnal Mebis, 2023)
Facing a period of adaptation to new habits, people will face many unfamiliar situations. Moreover, as consumers, people will be more thoughtful and detailed in making their choices on a product. Management must exercise greater caution when formulating a competitive strategy during habitual change if a company wants to keep and grow its customer base. This research aims to answer the question, "To what extent does knowledge sharing affect the use of social media and learning models in response to the goals of autonomous learning and autonomous universities?" we investigate the interplay of our study's components. Customers who have expressed an interest in purchasing an SME product will be surveyed using questionnaires. Purposive sampling with incidental sampling was used to administer the questionnaire to college and university students. 148 participants have been collected, and a research model structure is implemented in Partial Least Square analysis using SmartPLS software. Previous studies have shown no positive effect of the brand equity variable on consumers' propensity to purchase products from SMEs. The results show that the correlation of brand awareness of MSME products to brand equity is strongly influenced by brand awareness of MSME products which is given consistently on social media.